A review on China's Energy Storage Industry under the "Internet Plus" initiative. (9th October 2018) - Xie, Pinjie; Sun, Feihu; Wang, Lianghong; Liu, Pingkuo
Summary: In the context of China's "Internet Plus" era, the application of big data and energy storage technology etc. plays an important role in controlling the renewables of randomness and intermittence during the generation. This paper focuses on the development of China's Energy Storage Industry, summarizes the industrial situation and policy environment, analyses China's Energy Storage Industry by the PEST‐SWOT framework, and discusses the development trends and three cases under the "Internet Plus" initiative. At last, several recommendations are offered from energy storage system, development solutions, market design and international cooperation, aiming to cope with the issues concerning the development of China's Energy Storage Industry and future challenges. It is expected that such recommendations can be a boost to China's energy storage industry in the future. Abstract : Current situation of China's Energy Storage Industry is investigated. Policy environment is presented and analyzed. The PEST‐SWOT framework of China's Energy Storage Industry is analyzed. The development trends and three cases of China's Energy Storage Industry under the "Internet Plus" initiative are discussed. The suggestion on promoting the development of China's Energy Storage Industry is proposed from energy storage system, development solutions, market design, and international cooperation.